The video game and literary reading: new space for digital natives - Nieves Gutiérrez Ángel (Universidad de La Rioja, 2020)
We are facing a social reality in which reading is not produced also through books, but also to websites, forums, digital newspapers, or video games, configuring all of them as new spaces for reading. In recent years, they were published in the 1980s, although they were largely sold in the 1990s. At the same time, they offered an ideal tool for students to build and develop their knowledge. In this sense, video games are closely linked to reading, and have brought about a change in our attitudes towards reading and writing, and a new channel for transmitting narratives. The present work analyzes a series of video games in which there is a reference to literary figures, or they are direct adaptations of the works.